Impact of incentives for greener battery electric vehicle charging – A field experiment. (February 2022) - Kacperski, Celina; Ulloa, Roberto; Klingert, Sonja; Kirpes, Benedikt; Kutzner, Florian
Abstract: Battery electric vehicles generate a significant share of their greenhouse gas emissions during production and later, when in use, through the energy used for charging. A shift in charging behavior could substantially reduce emissions if aligned with the fluctuating availability of renewable energy. Financial incentives and environmental appeals have been discussed as potential means to achieve this. We report evidence from a randomized controlled trial in which cost-free and "green" charging was advertised via email notifications to customers of a charging service provider. Emails invited to charge during midday hours (11:00 to 15:00) of days with high predicted shares of renewable energy. Results show a significant increase in the number of charging processes in the critical time, and in the amount of energy charged (kWh), despite only marginal monetary savings of 5€ on average. A further increase in kWh charged was observed on weekends. Under the assumption that these charging processes replaced regular overnight charging at home, this represents reduction in CO2 emissions of over 50%. Highlights: Field experiment to steer electric vehicle drivers' charging behavior. EV driving customers of charging service provider participated in RCT. Financial-environmental incentive intervention ("free-when-green") was tested. Incentive significantly increased charging in select low-emission timeslots. Reductions in GHG emissions due to steered charging were calculated.